Feeding behaviours in infancy of children later diagnosed with autism spectrum disorder - Varma, Chaitanya; de Souza, Nandita (International Journal of Contemporary Pediatrics, 2023)
Background: Autism spectrum disorder, the fastest growing childhood neurodevelopmental diagnosis, shows good outcomes with early intervention. The search for behavioral early markers is an important area of research. Studies of breastfeeding and weaning behaviours in autism have reported characteristic patterns which could be early indicators of this condition. Methods: The study was a cross sectional survey of breastfeeding and weaning patterns during the first year of life in 50 children aged 15 months to 5 years, including 25 with ASD and 25 Neurotypical children. A semi-structured interview schedule and the brief assessment of mealtime behavior in children scale was used to elicit feeding history from their mothers. Data was analysed using descriptive statistics and tests of significance. Results: There were significant differences in the patterns of early feeding of children with ASD, compared to the NT children. 64% ASD children showed dysregulated vigorous sucking during breastfeeding, without knowing when to stop. 52% of them breast fed for more than 40 minutes per feed. 68% continued to breastfeed beyond the age of 2 years. A significant proportion of ASD children also showed weaning difficulties such as limited variety (40%), food refusal (36%) and disruptive mealtime behaviour (32%). Conclusions: Children with ASD show significantly more challenging breastfeeding and weaning behaviours in infancy, compared to NT children. These patterns could be identified by parents and health workers in early child development as possible early signs of ASD and prompt referral for further diagnostic evaluation.